2016
DOI: 10.12737/20999
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between the ULF wave power spatial distribution and auroral oval boundaries

Abstract: waves, but it could be significant for the development of more adequate models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This paper studies ULF power in solar wind and on ground over monthly and solar cycle time scales. Ground ULF waves in Pc5 frequency range are known to be driven predominantly by solar wind speed (Tanskanen et al, 2005) and to be related to the Kelvin-Helmholtz mechanism (Nykyri, 2013) and auroral substorm processes (Pilipenko et al, 2001;Kozyreva et al, 2016). ULF waves on ground as well as in solar wind have been examined for decades (Jacobs et al, 1964).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper studies ULF power in solar wind and on ground over monthly and solar cycle time scales. Ground ULF waves in Pc5 frequency range are known to be driven predominantly by solar wind speed (Tanskanen et al, 2005) and to be related to the Kelvin-Helmholtz mechanism (Nykyri, 2013) and auroral substorm processes (Pilipenko et al, 2001;Kozyreva et al, 2016). ULF waves on ground as well as in solar wind have been examined for decades (Jacobs et al, 1964).…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear, which mechanisms produce the Pc5 wave power in the auroral zone. However, based on studies on some features of storm-time substorms (Pilipenko et al, 2001;Kozyreva et al, 2016), Pc5 wave power variations in that region are connected to the auroral electrojet and fieldaligned currents in a way that is not presently understood. Higher than magn.…”
Section: Discussionmentioning
confidence: 99%
“…Even when one auroral station is in darkness while the other is in sunlight, rather than differing by an order of magnitude, Σ (N) and Σ (S) are usually much closer to a factor of 2. It is important for the considered problem, because the "epicenters" of the Pc5 power (Kozyreva et al, 2016) and TCV amplitude (Sibeck et al, 1996) are typically located near the equatorward auroral oval boundary.…”
Section: Additional Factors Influencing Ground Magnetometer Observationsmentioning
confidence: 99%
“…For example, in Kozyreva et al. (2016) and Martines‐Bedenko et al. (2018) it was found that a latitudinal maximum of Pc5 pulsations is localized around the equatorward auroral boundary.…”
Section: Discussionmentioning
confidence: 99%
“…This may be important for ULF waves. For example, in Kozyreva et al (2016) and Martines-Bedenko et al (2018) it was found that a latitudinal maximum of Pc5 pulsations is localized around the equatorward auroral boundary. The way to estimate contribution of auroral precipitation into the ionospheric conductance is to combine the IRI model and the OVATION-prime model, which gives information on the location of the auroral oval (Pilipenko et al, 2021).…”
Section: Discussionmentioning
confidence: 99%